ANALYSIS OF LEARNING STRATEGIES IN OVERCOMING STUDENTS’ DIFFICULTIES IN LEARNING MATHEMATICS - Yuni Apriani Siahaan; Jesika Replesia Rajagukguk (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2026)
This study aims to analyze learning strategies used to overcome students' difficulties in learning mathematics. The analysis is based on a review of 20 national journal articles published between 2021 and 2026. Mathematics plays an important role in education because it helps develop logical, critical, and systematic thinking skills in students. However, many students still experience difficulties in understanding mathematical concepts due to low learning motivation, lack of participation in classroom activities, and limited understanding of problem contexts. This study uses a qualitative descriptive approach through a Systematic Literature Review (SLR). Data were collected by searching articles from Google Scholar, Garuda, and SINTA databases using keywords related to mathematics learning difficulties and learning strategies. Articles were selected based on inclusion criteria covering relevance to the topic, discussion of mathematics learning difficulties, and explanation of strategies used. The results show that the most frequently recommended strategy is the use of instructional media (concrete and visual), appearing in 14 of 20 articles (70%), followed by graduated practice exercises (9 articles, 45%), motivation enhancement (6 articles, 30%), parental collaboration (5 articles, 25%), and contextual learning (4 articles, 20%). These findings imply that effective mathematics learning must be varied, concrete, contextual, and supportive of students' thinking development.